2021
DOI: 10.29271/jcpsp.2021.05.553
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Putative Cancer Stem Cell Markers, CD44 and CD133, are Correlated with Pathological Tumour Stage in Gastric Adenocarcinoma

Abstract: Objective: To analyse partial and total gastrectomy specimen in items of immunohistochemical staining of the stem cell CD44 and CD133; and to determine their relationship to pathological stage, other clinicopathological prognostic parameters, and their predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Oct4, Nanog, and Ascl2 are the main genes for intestinal stem cells to maintain self-renewal and cell dedifferentiation 32. CD133, CD44, and ALDH are critical surface markers in cancer stem cells [ 19 , 32 ]. In this study, we found that CSCs derived from CRCs have increased expression levels of stemness genes and tumor stem cell surface markers.…”
Section: Discussionmentioning
confidence: 99%
“…Oct4, Nanog, and Ascl2 are the main genes for intestinal stem cells to maintain self-renewal and cell dedifferentiation 32. CD133, CD44, and ALDH are critical surface markers in cancer stem cells [ 19 , 32 ]. In this study, we found that CSCs derived from CRCs have increased expression levels of stemness genes and tumor stem cell surface markers.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are characterized by self-renewal, pluripotency, and expression of stem cell markers, which can increase the malignant progression of the tumor [ 2 , 4 ]. Studies have shown that CSCs exist in cervix cancer, and their potential stem cell markers include CD133, ALDH1, CD49, OPN or SOX2 [ 5 ]. How to target stem cell markers and inhibit CSC characteristics of cervix cancer is an urgent problem needed to be addressed to improve the prognosis of patients with advanced cervix cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%